STUDENTS' PERCEPTION ON ANXIETY IN SPEAKING ENGLISH AT SENIOR HIGH SCHOOL - Juwi P. C. Saroinsong; Nihta Liando; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2022)
The aim of this research is to find out the students’ anxiety in speaking English. In this study, the researcher used a descriptive quantitative approach in order to answer the proposed questions. The sample that was taken from one class only with the total of students were 36 students. Therefore, it can be said that one of three indicators the represent the anxiety of students in speaking English, the most dominant is the second indicator, namely text anxiety where students feel the most anxious and worried when faced with formal situations such as exams, tests, midterm exams or practical exam. The test anxiety indicator is the indicator that covers the most questions in the distributed questionnaire, which includes 15 questions related to it, so it can be said that there is a need for a special method that can be a solution to students’ anxiety in speaking which is dominated by fear informal learning situations. Thus, for students who have been felt or experienced speaking anxiety, perhaps that students study hard to minimize their anxiety such as increasing reading books, listening to music, watch western movies without subtitles. Finally, always be brave, confident, don’t be afraid to try to speak with others and speaking skills. Furthermore, the students need to implement more in speaking and for the further researcher, perhaps this research can be used as a source of reference for their research.